The Influence of Using Pictures in Teaching English - Agustina, Devi (The Explora, 2020)
This research was conducted at MAN Binjai to improve Teaching English Competence by using the pictures as a media with the first year students of X-A through an Experimental Research Project. Since this research is done based on a qualitative method it means that, it does not need to state the hypothesis in the case of doing research, for it is based on the library or through book review. The writer here is eagerly concemed with the problem of using pictures or visual materials in teaching leaming process to beginners, especially the students of MAN levels. Practically, those four language skills can be taught by using pictures or visual materials, the radio ín particularly applied by Imhoof Maurice, a project director for the Radio Language Arts Project in Kenya and a senior program officer at the Academy for Educational Development in Washington DC, have a great influence in the process of teaching learning interaction, especially for the beginners So that is why, here the English teachers are suggested to use aids in teaching the students, (handling the class by showing various kinds of pictures). It is easier to the students to express what they want to say or tell if they look at the pictures or visual aids on the blackboard. for instance. Through pictures the students can be asked to repeat or mention many kinds of action based on the given pictures, they are asked to repeat sentence patterns given, and then ask them to make sentences by themselves based on the rules given firstly by the teacher. In general sense, teaching the students or the beginners by using pictures or visual materials can give them the meanings of the words of the pictures intrinsically and automatically. In short we can conclude that, teaching English by using pictures or visual materials to beginners have a great influence in the students’ understandings aid grasping the meanings of the words. The beginners will study English seriously and easily through looking at the colorful pictures shown to them.